2021
DOI: 10.3389/fvets.2021.742785
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Calf Pneumonia Outbreaks in Italian Dairy Herds Involving Mycoplasma bovis and Other Agents of BRD Complex

Abstract: Mycoplasma bovis is increasingly recognized worldwide as an important cause of disease with major welfare and production impairments on cattle rearing. Although it was detected in veal calves and beef cattle, little is known on the infection impact and on its temporal morbidity pattern in Italian dairy herds. Thus, this study aimed to investigate the involvement of M. bovis on fatal calf pneumonia outbreaks that occurred during 2009–2019 in 64 Italian dairy farms. Furthermore, a deeper diagnostic workup of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The prevalence of P. multocida varies widely ranging from a few percent to over eighty [ 5 , 8 , 14 , 15 , 16 , 17 , 19 , 20 , 28 , 32 , 35 , 36 , 37 , 38 ]. Similar to our results, Paller et al noted that the highest prevalence occurred for P. multocida (58.64%) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of P. multocida varies widely ranging from a few percent to over eighty [ 5 , 8 , 14 , 15 , 16 , 17 , 19 , 20 , 28 , 32 , 35 , 36 , 37 , 38 ]. Similar to our results, Paller et al noted that the highest prevalence occurred for P. multocida (58.64%) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their study was conducted on a smaller group, as well as a different region of Poland [ 44 ]. The prevalence of M. bovis shown by researchers from other regions of the world varies even more: from a few percent to over eighty [ 8 , 15 , 16 , 19 , 28 , 32 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. bovis is a slow growing, host-specific commensal that has been implicated in a number of bovine diseases including mastitis, arthritis, pneumonia, and in some reproductive losses, 31 and particularly in the development of lung lesions in cattle. 32 Whilst it is accepted that M. bovis can be causal for respiratory disease outbreaks in cattle, particularly when present in combination with other BRDcausing microorganisms, 33,34 this study is the first to identify that cattle entering the Australian feedlot system at induction are not carrying detectable levels of M. bovis in their upper respiratory tract compared to cattle located in the hospital pen at the same location. Our findings are similar to those of a Canadian study that reported low M. bovis prevalence in animals at induction (1.7%) which increased over time in the feedlot (≤15 days -72.2%, 55 days 85.7%).…”
Section: Mycoplasma Bovis As An Integrated Player In Brd Risk In Feedlotmentioning
confidence: 86%
“…Among these bacteria, Pasteurella multocida ( P. multocida ), a pathogenic gram-negative bacterium, has been divided into three subspecies, five capsular serogroups, and 16 serotypes. P. multocida serogroup A is commonly isolated from both enzootic calf pneumonia of young dairy calves and shipping fever of weaned and stressed beef cattle ( 4 ). In Belgium between 2016 and 2018, analysis of the cattle samples from 128 BRD outbreaks found P.multocida with a detection rate of 89.1% ( 5 ).…”
Section: Introductionmentioning
confidence: 99%